Developing training for Data Safety Monitoring Board members: A National Institute of Allergy and Infectious Diseases case study. (December 2015) - Zuckerman, Judith; van der Schalie, Barbara; Cahill, Kelly
Background: Data Safety Monitoring Boards primarily review accumulating data on clinical trials and provide recommendations to sponsors on whether a protocol should continue as planned, be modified, or be terminated. Data Safety Monitoring Boards often provide their recommendations based upon accumulating data to which only their members are given access. Despite the substantial responsibilities assumed by Data Safety Monitoring Board members, there is limited information in the literature about the unique knowledge they must possess and, consequently, the training content needs that are required in order for them to fulfill their obligations. Purpose: This article describes how the National Institute of Allergy and Infectious Diseases identified the knowledge that Data Safety Monitoring Board members should acquire and the computer-based training they developed to address the learning needs of the National Institute of Allergy and Infectious Diseases assembled Data Safety Monitoring Board members. Methods: The National Institute of Allergy and Infectious Diseases conducted a comprehensive literature search and interviewed Data Safety Monitoring Board subject matter experts, including Data Safety Monitoring Board members and chairs from academic institutions, pharmaceutical companies, and the National Institutes of Health to (1) assess whether Data Safety Monitoring Board training is an identified need, (2) evaluate whether Data Safety Monitoring Board training has been developed, and (3) formulate suitable learning objectives. Data Safety Monitoring Board training modules were developed based on the identified learning objectives identified from the interviews. Results: Three Data Safety Monitoring Board training modules were developed and formatted for web-based access, which is free of charge to the public athttps://dsmblearningcenter.niaid.nih.gov . The modules include the following: an introduction to the objectives and purpose of Data Safety Monitoring Boards, the organization and responsibilities of Data Safety Monitoring Boards, and a review of statistical topics. Limitations: The complex concepts that Data Safety Monitoring Board members must apply to their deliberations and decisions require practice and application that come through hands-on experience. To build competency in the Data Safety Monitoring Board member role, not only does a member need to understand these complex concepts but also the member must have the opportunity to practice and apply this knowledge to real-life situations. Additional resources to facilitate practice and application of the complex issues that Data Safety Monitoring Boards deal with should be considered. The computer-based training is targeted to new and inexperienced Data Safety Monitoring Board members. Ongoing learning opportunities should be developed for experienced Data Safety Monitoring Board members. Non-English training must also be considered. Conclusion: The National Institute of Allergy and Infectious Diseases identified that training is not widely available for Data Safety Monitoring Board members to build the unique knowledge and skills necessary to serve on Data Safety Monitoring Boards. Consequently, National Institute of Allergy and Infectious Diseases developed publicly available web-based Data Safety Monitoring Board training modules for new or inexperienced members. Additional tools and resources are needed to help Data Safety Monitoring Board members acquire the knowledge and skills to serve their critical function in clinical research and to maximize research participant protections.